Motif disabilitas netra berprofesi sebagai pustakawan - Rahmat Alifin Valentino; Agus Rusmana; Ninis Agustini Damayani (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. The number of librarian with disability, particularly with limited ability to see or blind is not many. This research explores the motives of the blind on why becoming librarians. Research methods. This study used a qualitative research method with a phenomenological approach. Data collection techniques used observations and interviews. Sampling was decided purposively. Analysis data. Research analysis was conducted through the stages of data reduction, data display, and conclusion drawing. Data validation techniques were carried out using credibility tests. Results and Discussion. The motive to become a librarian refers to Alfred Schutz's phenomenological theory which can be divided into two categories: motives based on because-motive (Weil-Motiv), namely the hobby of reading, lack of reading material for blind people, and library facilities that support performance for librarians with visual disabilities. Motives based on the in-order-to motive (Um-zu-Motiv) are to change the social stigma of people with visual disabilities, increase readers’ interest in reading, socialize braille collections, increase economic levels, and increase relationships. Conclusion. The findings show that being a librarian with visual disabilities is oriented towards past and future motives.